2007
DOI: 10.1016/j.jvs.2006.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide digital subtraction angiography–assisted endovascular aortic aneurysm repair in the azotemic patient

Abstract: CO(2)-DSA is safe, can be used to guide EVAR, and provides outcomes similar to ICA-guided EVAR. CO2-DSA protects renal function in the azotemic patient by lessening the need for iodinated contrast and associated nephrotoxicity, but with the tradeoff of longer fluoroscopy and operating room times and increased radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 25 publications
2
65
0
8
Order By: Relevance
“…7,14-18 Also, a few studies have shown the accuracy of CO 2 -DSA in detecting ELs. 16,17,19 Huang et al reported that the sensitivity to detect any EL and both the sensitivity and specificity to detect type I ELs with CO 2 -DSA are acceptable. 7 However, for detection of type II ELs with CO 2 -DSA, the sensitivity and PPV are poor.…”
Section: Discussionmentioning
confidence: 99%
“…7,14-18 Also, a few studies have shown the accuracy of CO 2 -DSA in detecting ELs. 16,17,19 Huang et al reported that the sensitivity to detect any EL and both the sensitivity and specificity to detect type I ELs with CO 2 -DSA are acceptable. 7 However, for detection of type II ELs with CO 2 -DSA, the sensitivity and PPV are poor.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, placement of a guiding sheath could eliminate these problems. Carbon dioxide has been used to avoid adverse effects of ICM in diagnostic and EVAR procedures (5,14). However, since the use of carbon dioxide requires experience and special instruments, it is not widely used in our country, which is similar to the rest of the world.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the adverse effect of contrast media, carbon dioxide angiography and intravascular ultrasonography (IVUS) have been assessed as an alternative strategy in EVAR (5,6). Intravenous hydration with saline, low-, or iso-osmolar nonionic contrast media as well as lower doses of contrast media can minimize CIN (4).…”
mentioning
confidence: 99%
“…Carbon dioxide digital subtraction angiography is a good alternative for endovascular repair of aortic aneurysms in azotemic patients. 8 Approximately 80% less contrast medium is utilized with endovascular aortic aneurysm repair. 8 If the image quality of carbon dioxide digital subtraction angiography is equivalent to that of conventional subtraction angiography for visualizing endoleaks at the end of the procedure, it can exclude contrast medium usage completely and is more advantageous than intravascular US.…”
Section: Discussionmentioning
confidence: 99%